2016
DOI: 10.1111/jon.12384
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Etching on MRI in Patients with Microangiopathy

Abstract: In this preliminary case series, we describe patients with "susceptibility etching" on SWI who were also found to have profound coagulation impairment. While other comorbities may also contribute to this novel sign, we suggest that a possible etiology may be secondary to microvascular in situ formation of fine thrombi and/or emboli lodged into an area of vascular caliber reduction and maybe related to thrombotic microangiopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…3 Cerebral microbleeds have been also reported in septic shock patients with or without DIC and/or cardiac arrest. [14][15][16] Despite similar locations, microbleeds in these patients with microangiopathies were responsible for both white and grey matter damage, thalami and dentate nuclei impairment, contrasting with our poisoned patients. Histopathological data found microscopic infarctions in the splenium of the corpus callosum caused by thrombosis or embolism but not haemorrhages, highlighting the contribution of microangiopathy.…”
Section: Subcortical White Mattercontrasting
confidence: 65%
See 1 more Smart Citation
“…3 Cerebral microbleeds have been also reported in septic shock patients with or without DIC and/or cardiac arrest. [14][15][16] Despite similar locations, microbleeds in these patients with microangiopathies were responsible for both white and grey matter damage, thalami and dentate nuclei impairment, contrasting with our poisoned patients. Histopathological data found microscopic infarctions in the splenium of the corpus callosum caused by thrombosis or embolism but not haemorrhages, highlighting the contribution of microangiopathy.…”
Section: Subcortical White Mattercontrasting
confidence: 65%
“…Cerebral microbleeds have been also reported in septic shock patients with or without DIC and/or cardiac arrest 14–16 . Despite similar locations, microbleeds in these patients with microangiopathies were responsible for both white and grey matter damage, thalami and dentate nuclei impairment, contrasting with our poisoned patients.…”
Section: Discussionmentioning
confidence: 44%
“…The authors suggested an association of endothelial dysfunction, DIC and thrombotic microangiopathy as a common potential cause of MH in critically ill patients. 30 In our study and across all similar COVID-19 case series published to date, there was evidence of coagulopathy, but no patients met international consensus criteria for overt DIC. 4 14 31 This aligns with a recent study that suggests that COVID-19 coagulopathy is distinct from DIC.…”
Section: Discussionmentioning
confidence: 47%
“…This is supported by the relatively low rate of macroscopic hemorrhages in our study and previous studies (2,12,13), despite routine use of anticoagulation/antiplatelet treatment in COVID-19. Interestingly, hemorrhagic components are not always histopathologically evident in critically ill patients with SWI abnormalities either (33). The terminology may affect the clinical cost-benefit analysis of anticoagulation therapy and since microthrombi is a valid differential diagnosis, this semantic issue is of clinical importance.…”
Section: Discussionmentioning
confidence: 99%